Chemical Reactivity and Optical and Pharmacokinetics Studies of 14 Multikinase Inhibitors and Their Docking Interactions Toward ACK1 for Precision Oncology - Srivastava, Ruby (Frontiers in Chemistry, 2022)
Abstract: Activated Cdc42-associated kinase 1 (ACK1/ TNK2) is a non-receptor tyrosine that plays an important role in cell endocytosis, survival, proliferation, and migration. Mutation and overexpression of ACK1 are related to the prognosis and lead to various cancers. In this work, we have used the Conceptual Density Functional Theory (CDFT) based Computational Peptidology (CDFT-CP) method to study the chemical reactivity, bioactivity, and pharmacokinetics indices related to Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) of 14 multikinase inhibitors and its docking interactions to the ACK1 target sites. All inhibitors have a high blood-brain barrier (BBB) permeability with high human intestinal absorption (HIA) and low Caco-2 permeability rates. There is a considerable variation for predicted human ether-a-go-go-related gene (hERG) channel blockage, Salmonella typhimurium reverse mutation assay (AMES) carcinogenicity, honey bee, and Tetrahymena pyriformis (TF) toxicity. Ligand solubility for the inhibitors hit approached lower bounds, while lipophilicity was acceptable. Results indicated drug-like inhibitors with binding energies less than -6 kcal/mol for ACK1-Inhibitor Complexes. Since ACK1 is a key target for neurological diseases, inflammation, and immunological diseases also so the studies will help in providing potential strategies for the treatment of cancers and other diseases that require simultaneous targeting of multiple targets. It will also help as a reference or in drug repurposing for precision medicine in target therapies and for the development of novel inhibitors.